PROXIMATE COMPOSITION, MINERAL AND VITAMIN CONTENTS OF RAW MILK FROM WADARA AND BUNAJI BREEDS OF CATTLE IN BAUCHI STATE, NIGERIA - Dilla, M. J.; Mai, H. M.; Abdulkarim, M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was carried out to evaluate and compare the proximate, mineral and vitamin compositions of raw milk from Wadara and Bunaji cattle breeds. A total of 20 milk samples were collected, from 10 each breed of cow. The sampling was conducted in the morning, immediately after feeding to minimize milk degradation in each breed. A composite sample was prepared by pooling the milk and stored in sterilized containers to prevent contamination and transported to laboratory for analysis of proximate composition, mineral and vitamin contents. The result revealed no significant difference in ash content (0.75±0.04 vs 0.76±0.06%), fat (4.04±0.25 vs 4.17±0.28%), protein (3.14±0.94 vs 3.48±0.18%) and carbohydrate (3.83±0.47 vs 4.15±0.81%) as well as moisture (87.53±0.99 vs 87.90±0.39%) content. Mineral content indicated a significant (P<0.05) difference in copper (0.85±0.05 vs 0.92±0.05mg/l) and sodium (118.07±5.50 vs 124.51±7.99mg/l) levels among milk samples with Wadaraʹs milk significantly (P<0.05) higher in copper and sodium content than Bunaji milk, which is beneficial for individuals in need of more minerals. However, Bunaji′s milk was significantly (P<0.001) higher in vitamin E content (0.25±0.00 vs 0.55±0.00iu) which offers better antioxidant properties, while both breeds have similar contents of vitamin A (1242.40 ± 2.11 vs 1245.60 ± 0.00iu), B (8.97 ± 0.95 vs 9.27 ± 0.00iu), C (8.20 ± 0.80 vs 8.50 ± 0.00iu), D (40.78 ± 1.05 vs 41.50 ± 0.00iu), and K (44.30 ± 0.00 vs 44.70 ± 1.05iu). It can be concluded that Wadara and Bunaji breeds of cattle can be used for milk production. However, wadara milk is recommended for commercial production due to better mineral and vitamin E content.